2019
DOI: 10.5194/gc-2-39-2019
|View full text |Cite
|
Sign up to set email alerts
|

Building bridges between experts and the public: a comparison of two-way communication formats for flooding and air pollution risk

Abstract: Abstract. Urban centres worldwide are adversely affected by flooding and air pollution. Better-prepared citizens are crucial to limiting the impacts of these hazards, and both lay knowledge and personal experiences are important in complementing and challenging expert opinion. For the first time, this study offers a critical comparison of how different two-way communication formats have been used worldwide between experts and the public in relation to flooding and air pollution risk. Through a systematic revie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Some students (7 of 17) also commented on the personal and reassuring connection they had experienced in communicating with the scientists. In forging out a communication process based on traditional media, we hoped to make an inclusive, fun, and accessible two-way dialogue between scientist and class as called for by Loroño-Leturiondo et al (2019). In this way, we hoped to create a safe space to exchange ideas about geoscience and for the students to ask any questions that they wanted.…”
Section: Question 1: What Did You Think About Using Handwritten Lette...mentioning
confidence: 99%
“…Some students (7 of 17) also commented on the personal and reassuring connection they had experienced in communicating with the scientists. In forging out a communication process based on traditional media, we hoped to make an inclusive, fun, and accessible two-way dialogue between scientist and class as called for by Loroño-Leturiondo et al (2019). In this way, we hoped to create a safe space to exchange ideas about geoscience and for the students to ask any questions that they wanted.…”
Section: Question 1: What Did You Think About Using Handwritten Lette...mentioning
confidence: 99%
“…The relationship between adequate information provision and behavioral change has been found to be mixed (Cornes, et al, 2019;Chowdhury, et al, 2019). Several studies have found that provision of adequate information substantially influences behavioral change (Cook, et al, 2019;Moser, et al, 2011;Falco, et al, 2019;Leturiondo, et al, 2019). According to Feldman et al (2016), public receipt of sufficient information on scientific findings could translate into a behavioral change when certain activities either precede or proceed information sufficiency provision.…”
Section: Potential Lifesaving Preparedness Informationmentioning
confidence: 99%